Resistance Exercise in People With Stage-3 Chronic Kidney Disease: Effects of Training Frequency (Weekly Volume) on Measures of Muscle Wasting and Function - Geneen, Louise J.; Kinsella, Jodie; Zanotto, Tobia; Naish, Patrick F.; Mercer, Thomas H. (Frontiers in Physiology, 2022)
Background: Resistance training (RT) is a proven anabolic intervention in people living with and without chronic kidney disease (CKD). To date, there is a dearth of knowledge regarding the dose-response relationship of RT in the non-dialysis dependent CKD population. Therefore, we aimed to explore the effects of RT frequency (weekly volume) on established measures of muscle wasting and function in CKD. Methods: Twenty people with stage-3 CKD (CKD-3) were allocated to either a low frequency (one-session per week, RT1) or higher frequency (three-sessions per week, RT3) 12-week RT programme consisting of lower extremity strengthening exercises. The two RT programmes were not volume matched. Assessment outcomes before and after the intervention included measures of total and regional body composition, muscle size and architecture, strength, physical function, and uraemic symptoms. Results: Significant improvements over time in muscle size and architecture, strength, physical function, and uraemic symptoms were observed for both RT1 and RT3. Compared to RT1, participants who performed RT3 showed greater increases in vastus lateralis (VL) anatomical cross-sectional area (30.8% vs 13.2%, p<0.001) and pennation angle (36.3% vs 17.5%, p=0.008) after 12 weeks. In either group, there were no significant changes over time in mid-VL fascicle length, nor in measures of total body composition and upper arm muscle strength. Conclusions: Despite the group differences observed in the VL physiological adaptations, the strength and physical function responses, as well as the reductions of uraemic symptoms, were similar whether training once or thrice weekly. Therefore, performing RT just once per week may be an effective pre-habilitation strategy for people with CKD-3.